Integrasi Pembentukan Kepribadian Islami dan Kesejahteraan Psikologis Anak - Nur Kumala (Indonesian Journal of Educational Counseling, 2026)
This research examines the integration between the development of Islamic personality and children’s psychological well-being as the foundation for holistic character formation from early childhood to adolescence. This topic is increasingly relevant amid modern challenges such as digital media exposure, adolescent identity crises, and declining family communication, which require parents and educators to have adequate understanding in guiding children. Islamic personality is defined as moral character built upon fundamental Islamic values including faith, piety, trustworthiness, and noble conduct, grounded in the Qur’an and the example of Prophet Muhammad. Psychological well-being refers to the child’s inner condition of feeling secure, loved, and able to develop optimally, corresponding to the concept of nafs al-muthmainnah. These two aspects are interrelated; spiritual and moral foundations strengthen the child’s values, while emotional stability supports the effective internalization of Islamic principles. The study reviews character development across three stages: early childhood, which emphasizes adab, akhlak, and tauhid; middle childhood, characterized by cognitive, social-emotional, and moral-religious growth; and adolescence, which requires the strengthening of self-efficacy based on tawakkul. The findings conclude that character formation is gradual and interconnected, with spiritual values and supportive environments serving as key determinants in shaping an insan kaffah, an individual who is morally upright, intelligent, emotionally stable, and resilient